THE JULY 2005 FLOOD IN VEDEA RIVER HYDROGRPAHIC BASIN IN JULY 2005 - TOMA FLORENTINA-MARIANA (Aerul şi Apa: Componente ale Mediului, 2013)
The present paper is focused on some aspects of the flood that occured in the hydrographic basin of Vedea river, located in central part of the Teleorman Plain. Daily data of discharge flow recorded in 7 hydrologic stations (Buzeşti, Văleni, Alexandria, Tătărăştii de Sus, Teleormanu, Ciobani, Vârtoapele) were used for this study for the period 3-10 july 2005. The conditions of the flood occurence were analyzed, as well as its type. To draw the flood hydrograph and to calculate the flood parameters the Cavis software, developed by researchers in INHGA Bucharest, was used. The main results are: the 2005 flood was generated by the high amounts of precipitation fallen at the beginning of July in the area; they were followed by the increase of the discharge flows and by dams collapse; an extreme negative impact was identified at economic, social and ecologic levels.